Anorectal melanoma – a report - Raja, Hisham; S., Kumar; Alif Gul, Yunus Gul (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
A review of the English literature confirms that anorectal melanoma is a rare tumour with dismal prognosis. Delay in diagnosis and the inherent aggressive systematic activity of the tumour at the time of diagnosis have been postulated as factors contributing to the poor prognosis. Surgery has always been the mainstay of treatment with options of either a wide local excision (WLE) or abdomino-perineal resection (APR). Neither radiotherapy nor chemotherapy has shown encourage results in terms of increasing survival or reducing loco-regional recurrence. Recently there has been much interest in the use of interferon-α following surgery. We hereby report two cases encountered during a period of 6 month and discuss the management of this rare condition together with a brief literature review.